Effects of acute unilateral ovariectomy to pre-pubertal rats on steroid hormones secretion and compensatory ovarian responses - Cárdenas Mario; Chavira Roberto; Trujillo Angélica; Vieyra Elizabeth; Ramírez Deyra A; Morales-Ledesma Leticia; Domínguez Roberto (BMC, 2011)
Abstract In the present study we analyzed the existence of asymmetry in the secretion of steroid hormones in pre-pubertal female rats treated with unilateral ovariectomy (ULO) or unilateral perforation of the abdominal wall (sham-surgery). Treated rats were sacrificed at different times after surgery. Since sham-surgery had an apparent effect on the age of first vaginal estrous (FVE) and serum levels hormone, the results of the sham surgery groups were used to assess the effects of their respective surgery treatment groups. On the day of FVE, compensatory ovulation (CO) and compensatory ovarian hypertrophy (COH) were similar in animals with ULO, regardless of the ovary remaining in situ. In ULO treated animals, progesterone (P4) levels were higher than in animals with sham-surgery one hour after treatment but lower in rats sacrificed at FEV. Left-ULO resulted in lower testosterone (T) concentration 48 and 72 hours after surgery. In rats with Right-ULO lower T concentrations were observed in rats sacrificed one or 72 hours after surgery, and at FVE. ULO (left or right) resulted in lower estradiol (E2) concentrations one or 72 hours after treatment. In rats with Left-ULO, E2 levels were higher 48 hours after surgery and at FVE. Left-ULO resulted in higher levels of follicle stimulating hormone (FSH) five hours after surgery and at FVE. FSH levels were higher in rats with Right-ULO sacrificed on FVE. The present results suggest that in the pre-pubertal rat both ovaries have similar capacities to secrete P4, and that the right ovary has a higher capacity to secrete E2. Taken together, the present results support the idea that the effects of ULO result from the decrease in glandular tissue and changes in the neural information arising from the ovary.